Obraz kosmosu rodzinnego w prozie kobiecej pierwszej fali emigracji rosyjskiej (na materiale wybranych utworów Niny Berberowej i Iriny Odojewcewej) = The theme of family in prose of female prose Russian emigration of first wave (on the example of Nina Berberova and Irina Odoyevtseva) - Witczak, Patryk (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The following article is devoted to the reflection on the female writing on the example of prominent emigrants od the younger generation, namely Nina Berberova and Irina Odoyevtseva. In russian emigration`s cultural and literary situation, the problem of perception of the family, family relationships and family values becomes extremely relevant.
Keywords: Odojewcewa, Irina Władimirowna (1895-1990); Berberowa, Nina Nikołajewna (1901-1993); rosyjska emigracja; rodzina; russian emigration; family